Pengaruh Representasi Gender dalam Iklan Televisi Terhadap Persepsi Khalayak - Fitriyah, Marisatul; Hadi, M. Sofiyan; Izza, Nikmatul (Yayasan Cendekia Gagayunan Indonesia, 2025)
The phenomenon of pseudo-feminism in Indonesian advertising reflects how narratives of women’s empowerment are often reduced to mere marketing strategies, without bringing about substantial change in the representation of women. Using a qualitative research method with a visual semiotic analysis approach and in-depth interviews with young women as the primary audience, this study reveals the contradiction between progressive verbal messages and visuals that continue to objectify the female body. Findings show that 73% of the analyzed advertisements exhibit a dissonance between feminist narratives and conventional visual imagery, leading to cognitive confusion and psychological pressure on the audience. Moreover, digital participation through social media as a form of resistance to biased representation faces challenges such as unequal access, algorithmic dominance, and the attention economy. The main conclusion of this research highlights the urgency of ethical transformation in advertising practices and the strengthening of digital public spaces that are more democratic and inclusive.